Strategic Power : USA/USSR - Edited by Carl G. Jacobsen (London Macmillan, 1990)
This book highlights the impact and relevance of "strategic culture". Each section contains essays contrasting United States and Soviet perceptions on specific topics. Each section closes with a synthesizing commentary, to help readers to get a better sense of differences and similarities.
Include Index
Keywords: United States -- Soviet Union -- Military policy -- Strategy -- Nuclear warfare